Mapping undergraduate theses in the Qur’anic and Tafsir Studies Program at IAIN Pontianak - Ramadhan, Ahmad Fadhail; Hamzah, Nur; Khalil, Muhammad Amin; Wahyuni, Sri; Sahri, Sahri; Wasehudin, Wasehudin (Jurnal Iman dan Spiritualitas, 2025)
This article aims to map the trends of themes and topics discussed in the theses of students in the Qur'anic and Tafsir Studies Program at IAIN Pontianak and to relate them to the vision and mission of the study program and the socio-religious context of the community in West Kalimantan. In analyzing the data, this research employs a qualitative approach with thematic analysis on 20 thesis titles from the year 2024. The results of this study indicate that there is a connection between the students and the vision and mission of the Qur'anic and Tafsir Studies Program at IAIN Pontianak for 2024. The results of this research indicate that students have a connection with the vision and mission of the Qur’anic and Tafsir Studies Program at IAIN Pontianak for the year 2024. This is based on the scientific orientation, approaches, and accommodation towards the Borneo culture. The vision of the Qur’anic and Tafsir Studies Program emphasizes the importance of excellence and openness in the study of Islam and local Borneo culture. In addition, in the research, students also support the mission of the Qur’anic and Tafsir Studies Program, particularly in terms of scientific excellence and research in Islamic studies. The research theme of students also strengthens the cultural heritage that forms the identity of Islamic scholarship and Bornean culture. However, there are still few student studies that discuss religious moderation in the context of West Kalimantan, both from the aspect of social dynamics and the realities of religious practices. In addition, there is limited integration of interpretive approaches with other disciplines such as fiqh, sufism, and socio-political studies. This research recommends strengthening the academic policy direction of the study program to encourage research that is more relevant to the needs of the local community, religious moderation, and the socio-religious dynamics of the West Kalimantan community.